2010
DOI: 10.2478/s11535-010-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton community of the drinking water supply reservoir Borovitsa (South Bulgaria) with an emphasis on cyanotoxins and water quality

Abstract: The phytoplankton diversity, algal biomass, and selected physicochemical parameters were investigated in the drinking water reservoir (Borovitsa) located in the Kardzhali region, Bulgaria. Particular attention was given to Cyanoprokaryota and presence of cyanotoxins in the water samples. Twenty-nine species belonging to six divisions (Cyanoprokaryota, Chlorophyta, Zygnemophyta, Dinophyta, Euglenophyta and Bacillariophyta) were identified. The microscopic examination of the phytoplankton samples showed the domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…showed strong seasonal relationships with temperature [28], and this genera provided important sources of organic carbon and nutrients for the summer food web [29]. This is a health concern in some cases, as Synechococcus blooms can produce harmful toxins [30][31][32]. Thus, we should strengthen the prevention and treatment of Cyanobacteria Synechococcus blooms in warmer seasons.…”
Section: Discussionmentioning
confidence: 99%
“…showed strong seasonal relationships with temperature [28], and this genera provided important sources of organic carbon and nutrients for the summer food web [29]. This is a health concern in some cases, as Synechococcus blooms can produce harmful toxins [30][31][32]. Thus, we should strengthen the prevention and treatment of Cyanobacteria Synechococcus blooms in warmer seasons.…”
Section: Discussionmentioning
confidence: 99%
“…2). According to Pavlova et al (2006Pavlova et al ( , 2007Pavlova et al ( , 2013aPavlova et al ( , 2014, Pavlova (2007) and Georgieva et al (2015) (Pavlova, 2007;Pavlova et al, 2007) and LA type was reported once from Borovitsa by Teneva et al (2010b).…”
Section: Environmental Gradients and Cyanoprokaryotes Distributionmentioning
confidence: 97%
“…This study compiles and evaluates the currently available data on phytoplankton and relevant environmental data on Bulgarian WBs (mainly reservoirs and lakes) gathered during the period 2000-2015 (Stoyneva, 2003(Stoyneva, , 2010(Stoyneva, , 2014(Stoyneva, , 2015Beshkova and Botev, 2004;Kalchev et al, 2004;Traykov, 2005;Pavlova et al, 2006Pavlova et al, , 2013aPavlova et al, , 2014Pavlova et al, , 2015Beshkova et al, 2008aBeshkova et al, , 2008bBeshkova et al, , 2012Pavlova, 2007;Tsanev and Belkinova, 2008;Teneva et al, 2009Teneva et al, , 2010aTeneva et al, , 2010bTeneva et al, , 2011Teneva et al, , 2014Cheshmedjiev et al, 2010aCheshmedjiev et al, , 2013Stoyanov et al, 2012Stoyanov et al, , 2013Stoyanov et al, , 2016Stoyanov, 2014Stoyneva et al, 2013Belkinova et al, 2014;Dimitrova et al, 2014aDimitrova et al, , 2014bDochin andStoyneva, 2014, 2015;Dochin, 2015;Georgieva et al, 2015).…”
Section: Data Collection On Planktonic Cyanoprokaryotesmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation agrees with results of Ömerli Dam (Albay & Akçalan, 2003). Additionally, Teneva, Belkinova, Dimitrova-Dylgerova, Vlaknova & Mladenov, 2010a;Teneva, Mladenov, Belkinova, Dimitrova-Dylgerova &Dzhambazov, 2010b andDimitrova, Nenova, Uzunov, Shishinova &Stoyneva, 2014 showed that in Bulgaria (Borovitsa Vacha and Vaya reservoirs), a neighboring country with similar climatic conditions, and cyanoprokariotic blooms in September were always dominated by the genus Microcystis. M. aeruginosa was also found in several studied reservoirs in Turkey such as Hasan Uğurlu, Kemer, Çamlıdere, Derbent, Hirfanlı, Ömerli and Kadıköy Reservoirs (Fakıoğlu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%